Fracture Healing in Two Adult Patients With Hypophosphatasia After Asfotase Alfa Therapy. (17th May 2018) - Klidaras, Philostratos; Severt, Jacqueline; Aggers, Deborah; Payne, Jason; Miller, Paul D; Ing, Steven W
ABSTRACT: Infants and children with hypophosphatasia (HPP) treated with asfotase alfa show improvement in bone mineralization and motor function, but it is unclear whether the medication can affect fracture healing in adult HPP patients. We present the course of fracture healing in two adults with HPP on enzyme replacement. Case 1 is a 41‐year‐old female with infantile‐onset HPP who was wheelchair‐bound due to a nonhealing tibial fragility fracture sustained 3 years before and also had nonhealing femoral pseudofracture sustained 17 years before starting asfotase alfa therapy in December 2015. One month after medication initiation, she underwent elective osteotomy of tibia and fibula with intramedullary nail fixation. After 3 months of enzyme replacement, she was full weight‐bearing and radiographs demonstrated callus formation at osteotomy sites, and at 11 months of therapy, radiographs showed union of the osteotomies. By 11 months of asfotase alfa therapy, there was near resolution of the femoral pseudofracture without interval surgery at this site. Case 2 is a 61‐year‐old male who showed nonunion of a fragility fracture of the right femur 8 years prior, intramedullary nail fixation 6 years prior, and stress fracture of the left femoral diaphysis sustained 1 year before starting asfotase alfa in October 2015. A trial of teriparatide was unsuccessful in healing of these fractures. On asfotase alfa, radiographs revealed interval healing of the left femur fracture after 12 months and complete healing of the right femur fracture and near resolution of the left femur fracture after 16 months of medical therapy. These two adult patients with HPP showed significant clinical and radiographic improvements in a total of four recalcitrant fractures on enzyme replacement therapy with asfotase alfa. © 2018 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.